A Normalized Subband Adaptive Filter with Combined Regularization Parameter. Issue 24 (2019) - Shi, Long; Zhao, Haiquan
Abstract: Proposed is a novel variable regularization algorithm for normalized subband adaptive filter (NSAF) by employing the mixing parameter to combine a large regularization parameter with a small regularization parameter. The mixing parameter is derived by minimizing the energy of noise-free a posteriori subband error. The combined regularization parameter can vary from a small value to a large value. Therefore, the proposed algorithm exhibits fast convergence rate meanwhile obtains low steady-state misalignment. Experimental simulations demonstrate the effectiveness of our work.